2014
DOI: 10.2105/ajph.2014.302055
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Population Health and Health Inequalities: The Role of Fundamental Causes

Abstract: Objectives As a case study of the impact of universal versus targeted interventions on population health and health inequalities, we used simulations to examine (1) whether universal or targeted manipulations of collective efficacy better reduced population-level rates and racial/ethnic inequalities in violent victimization; and (2) whether experiments reduced disparities without addressing fundamental causes. Methods We applied agent-based simulation techniques to the specific example of an intervention on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 77 publications
2
53
0
Order By: Relevance
“…20 23 The method is also useful for quantitatively comparing interventions, such as universal versus targeted interventions, which have been the subject of much debate. 40 Here, we show that interventions to reduce unnecessary antibiotic use among young children could substantially reduce diarrhoeal rates. This work responds to recent calls for a consequentialist epidemiology 41 by providing an example application of methods which can further the aim of presenting epidemiological findings that are relevant to public health practice and implementation science.…”
Section: Discussionmentioning
confidence: 72%
“…20 23 The method is also useful for quantitatively comparing interventions, such as universal versus targeted interventions, which have been the subject of much debate. 40 Here, we show that interventions to reduce unnecessary antibiotic use among young children could substantially reduce diarrhoeal rates. This work responds to recent calls for a consequentialist epidemiology 41 by providing an example application of methods which can further the aim of presenting epidemiological findings that are relevant to public health practice and implementation science.…”
Section: Discussionmentioning
confidence: 72%
“…Recently, researchers simulated an agent population consisting of 4000 adults that matched the New York City population and further evaluated the impact that mobilizing collective efficacy had on racial/ethnic disparities in violent victimization in two different types of hypothetical contexts: (1) complete residential segregation by race; and (2) no segregation by race and income (see Figure 4; Cerda et al, 2014). Results indicated that increasing collective efficacy by a small amount for the entire population effectively reduced the population prevalence of victimization (Cerda et al, 2014).…”
Section: Translating Animal Research To Humans: a Population-levelmentioning
confidence: 99%
“…Results indicated that increasing collective efficacy by a small amount for the entire population effectively reduced the population prevalence of victimization (Cerda et al, 2014). However, assuming a context of residential segregation by race (which most closely resembled the observed New York City context), collective efficacy experiments benefitted Whites more than Blacks, preserving racial inequalities in victimization (Cerda et al, 2014). The only way to reduce Black-White inequalities in victimization was to reduce residential segregation.…”
Section: Translating Animal Research To Humans: a Population-levelmentioning
confidence: 99%
“…The study of infectious diseases (because of the contagious nature of many infections) has long embraced and incorporated some features of systems in analytical approaches (such as the need to account for transmission from individual to individual and consequent dependencies), but only recently have systems approaches garnered attention in other areas of health 10,11,12 . Two important factors have contributed to this trend.…”
Section: Systems Thinking In Healthmentioning
confidence: 99%
“…Moreover, the intensification of weather and climate extremes, the most visible impact of global warming on our everyday lives, can contribute to increasing the incidence of myocardial infarction, especially in the elderly 12,13 .…”
Section: A Systemic Approach: What For?mentioning
confidence: 99%